Study of marine ecotourism potential of cubadak island West Sumatera Province - Nofri Andri Yulan; Syafruddin Nasution; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The aim of study is to identify tourist object of cubadak island and its potential level for marine ecotourism by used of survey method. Both primary and secondary data were collected by meaning, interviewing, and investigating directly. Interviewing sampling method was used purposively, particularly for tourist sample were used as accidental sampling. The result showed that Cubadak Island has a big potential in marine tourism and possess a big chance to develop in marine ecotourism sector. It was showed by the suitability value of marine ecotourism development. The value was resulted through tourism supporter criteria, total scores of WTA and WTP, scores of economic potential, and SWOT analysis.Key Words: Potential, Marine Ecotourism, Cubadak Island